Accumulation of Astaxanthin Was Improved by the Nonmotile Cells of Haematococcus pluvialis. (5th February 2019) - Li, Feng; Cai, Minggang; Lin, Mingwei; Huang, Xianghu; Wang, Jun; Zheng, Xuehong; Wu, Shaoting; An, Yu
Abstract : The current commercial production of natural astaxanthin is mainly carried out using Haematococcus pluvialis vegetative cells in the "two-stage" batch mode. The motile vegetative cells are more sensitive to stress than nonmotile vegetative cells, thereby affecting the overall astaxanthin productivity in H. pluvialis cultures. In this study, we compared the differences between motile cells and nonmotile cells in astaxanthin productivity, morphological changes, the mortality rate, and the diameter of the formed cysts. The experimental design was achieved by two different types H. pluvialis cell under continuous light of 80 μ mol photons m −2 s −1 for a 9-day induction period. The highest astaxanthin concentration of 48.42 ± 3.13 mg L −1 was obtained in the nonmotile cell cultures with the highest the productivity of 5.04 ± 0.15 mg L −1 day −1, which was significantly higher than that in the motile cell cultures. The microscopic examination of cell morphological showed a large number of photooxidative damaged cells occurring in the motile cell cultures, resulting in higher cell mortality rate (22.2 ± 3.97%) than nonmotile cell cultures (9.6 ± 0.63%). In addition, the analysis results of cell diameter statistics indicated that nonmotile cells were more conducive to the formation of large astaxanthin-rich cysts than motile cells. In conclusion, the works presented here suggest that the accumulation of astaxanthin was significantly improved by nonmotile cells of H. pluvialis, which provided a possibility of optimizing the existing H. pluvialis cultivation strategy for the industrial production.